Implementation of the window-shopping learning model assisted with "padlet" to increase students' mathematics learning activity and motivation - Fazlika, Jihan; Sasongko, Luddy Bambang; Lefrida, Rita (Jurnal Gantang, 2024)
Student learning motivation will increase, which is determined by the teacher's ability to learn design. As a result, students are more interested in actively searching and finding their ideas. This study aims to determine increased student activity and motivation to learn mathematics on Limited trigonometric function. Researchers used the Window-Shopping learning model assisted by Padlet. This research is a collaborative Classroom Action Research. The subjects in this study are students of class XII-1 at Madani Integrated Model Senior High School in the 2023/2024 academic year. The stages in the research follow the flow of Kemmis and McTaggart and consist of planning, action, observation, and reflection. Data collection in this study was conducted by observing student activity during the teaching and learning process and using questionnaires. The results showed that students' learning activities are significantly increased. This happens more when they are involved in the learning process; consequently, students can build their knowledge. Students support each other, share ideas, and collaborate in constructing their knowledge. In addition, the results of this study are based on the completion of a student learning motivation questionnaire. Based on the questionnaire obtained in the first cycle, it amounted to 70.67%. In the second cycle, it increased by 11.35%. So, the total increase is 82.02%. This can be categorized in the predicate "good."